Growing teratoma syndrome in a chemotherapy naïve patient - Sarah Werner; Tricia Numan; Peter Frederick; Nicole Gaulin; Katherine Mager; Mohamed Desouki; Emese Zsiros (Gynecologic Oncology Reports)
Growing Teratoma Syndrome (GTS) is an exceptionally rare condition primarily observed in patients diagnosed with malignant germ cell tumors. It is characterized by the development of enlarging masses during or following the completion of appropriate chemotherapy, with normalization of previously elevated serum tumor markers, and a final pathologic assessment of the masses reveals benign mature teratomatous elements. The underlying mechanism of the benign teratomatous growth remains unclear. Multiple potential routes of dissemination have been proposed, with the peritoneum being the most reported site of metastasis.In this report, we present the case of an adolescent female patient diagnosed with an ovarian grade 1 immature teratoma, who developed disseminated peritoneal and mesenteric implants shortly after her initial surgery. The pathologic review of the implants demonstrated only mature teratomatous elements. Uniquely, the masses were identified in a chemotherapy naïve patient.